The “Hub and Spoke” (HandS) ECMO for “Resuscitating” Neonates with Respiratory Life-Threatening Conditions - Massimo A. Padalino (Children, 2021)
Background: Extracorporeal membrane oxygenation (ECMO) implantation for neonates with severe cardiorespiratory life-threatening conditions is highly effective. However, since ECMO is a high-risk and complex therapy, this treatment is usually performed in centers with proven expertise. Methods: A retrospective review of neonates, from January 2014 to January 2020, presenting with life-threatening conditions and treated by means of Hub and Spoke (HandS) ECMO in peripheral (spoke) hospitals. Data were retrieved from our internal ECMO registry. Protocols and checklists were revised and shared with all spoke hospitals located in North-Eastern Italy. Results: Eleven neonates receiving maximal respiratory and cardiovascular support at a spoke hospital underwent HandS ECMO management. All but three patients were affected by life-threatening meconium aspiration syndrome (MAS). The median ECMO support duration and hospitalization were four (range 2–32) and 30 days (range 8–50), respectively. All but two patients (with congenital diaphragmatic hernia), were weaned off ECMO and discharged home. At a mean follow up of 33.7 ± 29.2 months, all survivors were alive and well, without medications, and normal somatic growth. All but one had normal neuropsychological development. Conclusion: HandS ECMO model for neonates with life-threatening conditions is effective and successful. A specialized multidisciplinary team and close cooperation between Hub and Spoke centers are essential for success.